Social Welfare in the Sustainable Development of the Bitung Special Economic Zone in Bitung City of North Sulawesi Province - Meinhart Moningka, Runtukahu Joi; Niode, Burhan; Waworundeng, Welly (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
This research aims to analyze the social welfare of the community in the sustainable development of the Bitung Special Economic Zone in Bitung City, North Sulawesi Province. The research employs a qualitative descriptive method based on social welfare indicators according to the Republic of Indonesia Law Number 11 of 2009, Article 6, regarding social welfare, which stipulates that achieving social welfare involves several indicators, including social security, social empowerment, and social protection. The research informants were obtained using purposive sampling techniques, totaling 16 informants. Data analysis comprised stages of data reduction, data presentation, and drawing conclusions. The research findings indicate that in terms of social security, the government ensures access to health needs, encompassing clean water, adequate housing, and environmental sanitation, as well as educational needs. The government provides educational infrastructure for the residents in the Bitung Special Economic Zone, including the Program Indonesia Pintar (PIP) and Kartu Indonesia Pintar (KIP). Regarding social empowerment, the government assists the community through Micro, Small, and Medium Enterprises (MSMEs), supported by the Cooperative and MSME Office of Bitung City. Furthermore, the government provides social protection, including contributions for national health insurance (JKN) and the Prosperous Family Rice Program (Rastra). The conclusion of this research is that social welfare for the community in the sustainable development of the Bitung Special Economic Zone in Bitung City is carried out in accordance with the applicable laws and regulations.